A grounded theory approach to security policy elicitation. (8th October 2018) - Foley, Simon N.; Rooney, Vivien
Abstract : Purpose: In this paper, the authors consider how qualitative research techniques that are used in applied psychology to understand a person's feelings and needs provides a means to elicit their security needs. Design/methodology/approach: Recognizing that the codes uncovered during a grounded theory analysis of semi-structured interview data can be interpreted as policy attributes, the paper develops a grounded theory-based methodology that can be extended to elicit attribute-based access control style policies. In this methodology, user-participants are interviewed and machine learning is used to build a Bayesian network-based policy from the subsequent (grounded theory) analysis of the interview data. Findings: Using a running example – based on a social psychology research study centered around photograph sharing – the paper demonstrates that in principle, qualitative research techniques can be used in a systematic manner to elicit security policy requirements. Originality/value: While in principle qualitative research techniques can be used to elicit user requirements, the originality of this paper is a systematic methodology and its mapping into what is actionable, that is, providing a means to generate a machine-interpretable security policy at the end of the elicitation process.